Social Return on the investment of the elimination of the vertical transmission of Chagas, HIV / AIDS, HB and Syphilis: Case of a Municipality of the Province of Buenos Aires - Monteverde, Malena; Silvestrini, Constanza; Pereiro, Ana Cristina; Wolovich, Tamara; Ceriotto, Mariana; Castelli, Juan Manuel (Población y Salud en Mesoamérica, 2021)
Introduction: we seek to quantify the returns on investment associated with an intervention in the public health system of a Municipality of the Province of Buenos Aires, Argentina. This intervention consists of strengthening the strategy for the Elimination of Mother-to-Child Transmission of HIV Infection, Syphilis, Congenital Chagas Disease and Perinatal Hepatitis B Infection, a strategy called ETMI-PLUS. Methodology: the study (quantitative) is based on the Social Return on Investment (RSI) methodology. Ad-hoc definitions are established for the measurement of returns based on the information available from various sources: primary information from the Ministry of Health of the MAB; rates of congenital transmission of each disease reported to the National Health Surveillance System; detailed budgets of the resources assigned to the project by Fundación Mundo Sano and costs of treatments and supplies from official nomenclators. Results: for each argentinean peso invested in strengthening the ETMI-PLUS in the MAB, a return of almost 4 pesos would have been obtained thanks to the improvements in the vertical elimination of the 4 diseases and the reduction of cardiac complications in pregnant women. Conclusions: these results suggest the existence of a return / investment relationship favorable to the intervention, analyzed under a conservative analysis since savings for the health system are exclusively included and other dimensions of returns associated with improvements in results are excluded.